The global decline of freshwater megafauna. (8th August 2019) - He, Fengzhi; Zarfl, Christiane; Bremerich, Vanessa; David, Jonathan N. W.; Hogan, Zeb; Kalinkat, Gregor; Tockner, Klement; Jähnig, Sonja C.
Abstract: Freshwater ecosystems are among the most diverse and dynamic ecosystems on Earth. At the same time, they are among the most threatened ecosystems but remain underrepresented in biodiversity research and conservation efforts. The rate of decline of vertebrate populations is much higher in freshwaters than in terrestrial or marine realms. Freshwater megafauna (i.e., freshwater animals that can reach a body mass ≥30 kg) are intrinsically prone to extinction due to their large body size, complex habitat requirements and slow life‐history strategies such as long life span and late maturity. However, population trends and distribution changes of freshwater megafauna, at continental or global scales, remain unclear. In the present study, we compiled population data of 126 freshwater megafauna species globally from the Living Planet Database and available literature, and distribution data of 44 species inhabiting Europe and the United States from literature and databases of the International Union for Conservation of Nature and NatureServe. We quantified changes in population abundance and distribution range of freshwater megafauna species. Globally, freshwater megafauna populations declined by 88% from 1970 to 2012, with the highest declines in the Indomalaya and Palearctic realms (−99% and −97%, respectively). Among taxonomic groups, mega‐fishes exhibited the greatest global decline (−94%). In addition, freshwater megafauna experienced major range contractions. For example, distribution ranges of 42% of all freshwater megafauna species in Europe contracted by more than 40% of historical areas. We highlight the various sources of uncertainty in tracking changes in populations and distributions of freshwater megafauna, such as the lack of monitoring data and taxonomic and spatial biases. The detected trends emphasize the critical plight of freshwater megafauna globally and highlight the broader need for concerted, targeted and timely conservation of freshwater biodiversity. Abstract : Globally, freshwater megafauna populations declined by 88% from 1970 to 2012, with the highest declines in the Indomalaya and Palearctic realms (−99% and −97%, respectively). Among taxonomic groups, mega‐fishes exhibited the greatest global decline (−94%). In addition to population declines, major range contractions of freshwater megafauna have been observed, which is more pronounced in Europe than in the United States.